PROFESSIONAL ROLE OF TEACHERS IN ENSURING INTEGRATIVE EDUCATION ON NUTRITION AND HEALTH FOR PUPILS IN NORWEGIAN SCHOOLS (Comparative Professional Pedagogy, 2023)
This article focuses on analyzing the role of teachers in promoting healthy eating and preserving the health of pupils in Norwegian primary and secondary schools. Special attention is paid to the analysis of research on teaching the school subject «Food and Health» in Scandinavian countries, particularly in Norway. It has been established that this subject plays a crucial role in forming healthy life habits among pupils, not only by developing basic knowledge about nutrition and physical activity but also by fostering the ability to think critically about food choices and understanding the impact of nutrition on health. It is defined that the professional development of teachers who teach this subject becomes of paramount importance, as the competency of educators is crucial in preparing the future generation for a life in harmony with nature and their own health. Enhancing qualifications, familiarizing with the latest research, and developing practical skills are identified as a key to achieving this goal. It is discovered that the importance of integrating the «Food and Health» subject into the school curriculum is underscored not only by the requirements for teacher education but also by the necessity to adapt educational programs to contemporary conditions. Research findings indicate a growing need for qualified teachers with subject-specific education, which constitutes a significant direction for further professional development of educators in this field. It is found that teachers with subject-specific training in “Food and Health” feel that they do their job better, are more satisfied with teaching, and work more on updating the content of the “Food and Health” subject than teachers without formal education in this area. Given the importance of subject-specific teacher education for the quality of Food and Health education, in 2020, Norway introduced a master's degree in Food and Health as a part of the basic teacher education.The conclusion is made that both drawing attention to the importance of healthy eating and developing relevant skills in pupils, as well as the professional development of teachers in this direction, can not only contribute to improving national health but also serve as an example for other countries.
Keywords: Norway; teachers; school subject «Food and Health»; school curriculum; subject-specific teacher education